Kerja Sama Indonesia dan Denmark Dalam Pengembangan Energi Baru Terbarukan (EBT) Di Indonesia - Hasna Mandasari Tianotak; Melpayanty Sinaga; Marinus Yaung (Cenderawasih University, 2023)
As part of their energy cooperation, Indonesia and Denmark have signed a Memorandum of Understanding (MoU) in 2015, which was later upgraded to the Indonesian Denmark Energy Partnership Programme (INDODEPP) signed in 2022. This study aims to analyze the potential benefit arising from this energy cooperation. Data for this study was collected from secondary sources using a qualitative research method. This study found that this cooperation provides mutual benefits for both countries, with Indonesia gains the most. Indonesia has abundant renewable energy resources, while Denmark is a leading country, with a long tradition in the development and utilization of new renewable energy. These conditions offer Indonesia the opportunity to benefit from a partnership with Denmark in the development of renewable energy and help Indonesia with future energy provision. In addition, this cooperation has improved Indonesia’s energy supply prospects, as indicated by the development of a wind power plant and a hybrid power plant, which aligns with Indonesia’s target of achieving 23% renewable energy by 2025.KEYWORDSAbundant Resources; Cooperation; Partnership; Renewable Energy